TGF-β signalling and liver disease - Fabregat, Isabel; Dooley, Steven (The FEBS journal, 2016)
The transforming growth factor-beta (TGF-β) family signalling pathways play essential roles in the regulation of different cellular processes, including proliferation, differentiation, migration or cell death, which are essential for the homeostasis of tissues and organs. Because of the diverse and pleiotropic TGF-β functions, deregulation of its pathways contributes to human disease. In the case of the liver, TGF-β signalling participates in all stages of disease progression, from initial liver injury through inflammation and fibrosis, to cirrhosis and cancer. TGF-β has cytostatic and apoptotic effects in hepatocytes, promoting liver differentiation during embryogenesis and physiological liver regeneration. However, high levels of TGF-β, as a consequence of chronic liver damage, result in activation of stellate cells to myofibroblasts and massive hepatocyte cell death, which contributes to the promotion of liver fibrosis and later cirrhosis. During liver tumorigenesis, TGF-β may behave as a suppressor factor at early stages; however, there is strong evidence that overactivation of TGF-β signalling might contribute to later tumour progression, once cells escape from its cytostatic effects. For these reasons, targeting the TGF-β signalling pathway is being explored to counteract liver disease progression. In this review, we aim to shed light on the state-of-the-art in the signalling pathways induced by TGF-β that are involved in different stages of liver physiology and pathology.
Gesehen am 17.06.2019